2013
DOI: 10.3892/mco.2013.180
|View full text |Cite
|
Sign up to set email alerts
|

Differences in estrogen and progesterone receptor expression in endometrial polyps and atrophic endometrium of postmenopausal women with and without exposure to tamoxifen

Abstract: Abstract.Postmenopausal women who use tamoxifen present with an increased incidence of endometrial alterations, such as polyps and hyperplasia, in addition to a higher risk of malignant endometrial neoplasms. Among these endometrial changes, polyps are the most common, with a pathogenesis associated with hormonal influence. The objective of this study was to compare the expression of estrogen receptors (ERs) and progesterone receptors (PRs) in endometrial polyps from tamoxifen users with that in endometrial po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“… 6 Previous studies have suggested that short-acting or slowly released progesterone hormone in combination with hysteroscopic resection was significantly effective in preventing postoperative recurrence of endometrial polyp. 7 - 9 …”
Section: Introductionmentioning
confidence: 99%
“… 6 Previous studies have suggested that short-acting or slowly released progesterone hormone in combination with hysteroscopic resection was significantly effective in preventing postoperative recurrence of endometrial polyp. 7 - 9 …”
Section: Introductionmentioning
confidence: 99%
“… 8 Their lipophilic structure allows estrogen to pass freely through the cell membrane and bind to the ER in the nucleus, controlling the expression of several genes, including those that encode PR and growth factors. 19 Exposure to estrogen unopposed by progesterone promotes the activation of oncogenes and the inactivation of tumor suppressor genes, impairing cell cycle regulation and leading to dysfunction of the proteins involved in tumor invasion and progression. 19 , 33 An imbalance between cell proliferation and apoptosis, influenced by the concentration of sex steroids, is thought to be one of the mechanisms underlying the development of endometrial disorders, either benign or malignant.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Exposure to estrogen unopposed by progesterone promotes the activation of oncogenes and the inactivation of tumor suppressor genes, impairing cell cycle regulation and leading to dysfunction of the proteins involved in tumor invasion and progression. 19 , 33 An imbalance between cell proliferation and apoptosis, influenced by the concentration of sex steroids, is thought to be one of the mechanisms underlying the development of endometrial disorders, either benign or malignant. 15 , 34 , 35 Thus, determining endometrial hormone response in the normal endometrium, as well as in benign, premalignant, and malignant lesions is very important for the characterization of potentially malignant changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the primary application of tamoxifen exploits its antagonistic effect on ER in the breast, its dual agonistic effect in the uterus has been shown to increase the risk for development of new leiomyoma, increase the size of existent uterine leiomyomas, and induce cystic and edematous changes as a result of elevated PR expression 13, 14, 15. Although IDC and ILC are known to metastasize to the common sites of the liver, lung, bone, peritoneal, and retroperitoneal spaces, it is likely because of proliferative changes in the endometrium with increased vascularization observed with tamoxifen exposure secondary to overexpression of PR that creates a “primed” hospitable environment for tumor seeding.…”
Section: Discussionmentioning
confidence: 99%